2013
DOI: 10.1177/1938965513496315
|View full text |Cite
|
Sign up to set email alerts
|

Tapping Mindfulness to Shape Hotel Guests’ Sustainable Behavior

Abstract: The characteristic of mindfulness is ascribed to people who have a relatively greater awareness of their surroundings and of other people. This study finds that assessing guests’ mindfulness helps hoteliers make those guests aware of and responsive to hotels’ sustainability practices. This process invokes specific elements of mindfulness, including guests’ concern for society and others, their preferences for mindful information services, the benefits they seek from a hotel experience, and their demographic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 55 publications
3
84
0
Order By: Relevance
“…There is consensus that consumers' perceptions regarding the magnitude of environmental degradation (Han, Hsu, Lee, & Sheu, 2011), consumers' environmentalism (Millar, Mayer, & Baloglu, 2012) and mindfulness (Barber & Deale, 2014) stimulate participation in green initiatives and the selection of hotels with green orientation (Barber, 2012;Prud'homme & Raymond, 2013). The seminal study of Khan (2003) supports that eco-tangibles (i.e.…”
Section: Consumers' Perceptions Towards Green Hotel Initiativesmentioning
confidence: 94%
See 1 more Smart Citation
“…There is consensus that consumers' perceptions regarding the magnitude of environmental degradation (Han, Hsu, Lee, & Sheu, 2011), consumers' environmentalism (Millar, Mayer, & Baloglu, 2012) and mindfulness (Barber & Deale, 2014) stimulate participation in green initiatives and the selection of hotels with green orientation (Barber, 2012;Prud'homme & Raymond, 2013). The seminal study of Khan (2003) supports that eco-tangibles (i.e.…”
Section: Consumers' Perceptions Towards Green Hotel Initiativesmentioning
confidence: 94%
“…Also, prior work has demonstrated that consumers may experience a higher level of sensitivity to justice when consuming luxury products (Kivetz & Simonson 2002). Elaborating on these findings, an interesting research avenue involves the examination of consumers' participation in green practices when consuming luxury hotel services (Barber & Deale, 2014).…”
Section: Current Issues In Tourismmentioning
confidence: 98%
“…A greater mindfulness of people and their environment enables hoteliers to increase their customers' sustainable behaviour (Barber & Deale, 2014). Repeated and enhanced mindfulness of a place, and its people's long-term wellbeing, can create in a person a sense of care, connectedness, belonging, and a bond with that place, which results in empathy.…”
Section: Introductionmentioning
confidence: 99%
“…Increased mindfulness implies thoughtful awareness of behavior [52] and may promote reflection on one's consumption activity and greater care in choice-making [19,54]. Mindful consumers examine the particular qualities of a situation before deciding on a course of action, rather than relying on established categories and habits [37,55]. As specified in one of the principles of socio-cognitive mindfulness, being open to new information generates cognitive routes for creativity, insight making, cognitive flexibility, self-acceptance, and personal responsibility [56].…”
Section: Socio-cognitive Mindfulness and Sustainable Consumptionmentioning
confidence: 99%
“…A more mindful individual develops a capacity to perceive and understand phenomena from multiple standpoints and to shift between perspectives as and when needed, generating more choice and response options [56]. Growing awareness and attentiveness facilitate a better understanding of the situation of others [55], including the social conditions of production and consumption and associated environmental consequences [40]. Thus, a more mindful individual may be more conscious with regard to the environmental and social consequences of their consumption instead of thoughtlessly following established consumption routines or norms.…”
Section: Socio-cognitive Mindfulness and Sustainable Consumptionmentioning
confidence: 99%